2018
DOI: 10.17957/ijab/15.0493
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Indigenous and Exotic Maize Hybrids for Grain Yield and Quality Traits under Heat Stress

Abstract: Heat stress is a major environmental constraint in crop production, worldwide. Identification and selection of suitable cultivars and traits for high temperature tolerance is vital to produce heat resilient genotypes. To find out superior genotypes and plant parameters, 14 maize hybrids of local and exotic origin, were evaluated under heat stress conditions. Evaluation of maize genotypes was done for morphological, phenological and quality related traits i.e., days to 50% tasseling, days to 50% silking, plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
5
10
0
Order By: Relevance
“…As grain yield is a complex, polygenic trait that is greatly influenced by the surrounding environment, the direct selection of genotypes based on grain yield is not an appropriate option. Section based on associated traits could prove more fruitful for the development of superior genotypes [23]. In current studies, newly developed wheat crosses were evaluated under optimal and heat stress conditions, and significantly positive associations were found between GY and associated traits.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As grain yield is a complex, polygenic trait that is greatly influenced by the surrounding environment, the direct selection of genotypes based on grain yield is not an appropriate option. Section based on associated traits could prove more fruitful for the development of superior genotypes [23]. In current studies, newly developed wheat crosses were evaluated under optimal and heat stress conditions, and significantly positive associations were found between GY and associated traits.…”
Section: Discussionmentioning
confidence: 98%
“…The presence of sufficient genetic variability among male and female parents and their cross combinations allows further assessment of these parental lines for combining ability analysis. Many researchers showed that the presence of significant diversity among cultivated germplasm from the warmer regions could be used for the development of heat resilient, climate-smart verities for heat prone areas [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Correlation coefficient analysis was carried out to compute degree and direction of correlation between different plant traits under both conditions. Furthermore, principal component (PCA) and agglomerative hierarchical cluster analysis (AHC) were used to characterize maize hybrids for their heat tolerance as introduce by Sneath and Sokal (1973) and used by Yousaf et al (2018). Two statistical packages i.e.…”
Section: Statistical Data Analysismentioning
confidence: 99%
“…Increase in anthesis-silking interval (ASI) due to desynchronization of male and female plant parts results into reduced pollination, poor fertilization and seed setting which leads to drastic reduction in kernel yield (Cicchino et al, 2010;Dass et al, 2010). Furthermore, reduction in kernel yield is also significantly associated with the reduction in photosynthetic ability, thousand kernel weight, plant biomass, cell membrane thermostability, number of kernels per cob and shelling percentage (COŞKUN et al, 2011;Yousaf et al, 2017;Yousaf et al, 2018 andNoor et al, 2019). These findings suggest that there is an utmost need for the development of heat resilient maize hybrids, having the ability to withstand harsh climatic conditions like heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al (2017) also screened maize inbred lines through Temperature induced response (TIR) technique and revealed that tolerant maize inbred lines expressed more root and shoot dry weights than susceptible inbred lines. Thus, in order to produce heat resilient genotypes, it is a regular program of researchers to identify and screen suitable cultivars and traits for high temperature stress (Yousaf et al, 2018). These findings further provided the support that suitable strategies can be adopted for improving the high yielding maize materials for heat tolerance and showing satisfactory yields in a cost effective manner (Slafer, 2003;Khan et al, 2010;Tiwari and Yadev, 2018).…”
Section: Discussionmentioning
confidence: 90%